Jascha Heifetz : early years in Russia - Kopytova, G. V.; Starkova-Heifetz, Albina (Russian music studies (Bloomington, Ind.), 2013)
Notoriously reticent about his early years, violinist Jascha Heifetz famously reduced the story of his childhood to "Born in Russia. First lessons at 3. Debut in Russia at 7. Debut in Carnegie Hall at 17. That's all there is to say." Tracing his little-known upbringing, this book uncovers the events and experiences that shaped one of the modern era's most unique talents and enigmatic personalities. Using previously unstudied archival materials and interviews with family and friends, this biography explores Heifetz's meteoric rise in the Russian music world - from his first violin lessons with his father, to his studies at the St. Petersburg Conservatory with the well-known pedagogue Leopold Auer, to his tours throughout Russia and Europe. Spotlighting Auer's close-knit circle of musicians, the author underscores the lives of artists in Russia's "Silver Age" - an explosion of artistic activity amid the rapid social and political changes of the early twentieth century.